Volumetric Blood Flow in Transjugular Intrahepatic Portosystemic Shunt Revision Using 3‐Dimensional Doppler Sonography. (1st February 2015) - Pinter, Stephen Z.; Rubin, Jonathan M.; Kripfgans, Oliver D.; Novelli, Paula M.; Vargas-Vila, Mario; Hall, Anne L.; Fowlkes, J. Brian
Abstract : Objectives: Three‐dimensional (3D)/4‐dimensional (4D) sonographic measurement of blood volume flow in transjugular intrahepatic porto systemic shunt revision with the intention of objective assessment of shunt patency. Methods: A total of 17 patients were recruited (12 male and 5 female; mean age, 55 years; range, 30–69 years). An ultrasound system equipped with a 2.0–5.0‐MHz probe was used to acquire multivolume 3D/4D color Doppler data sets to assess prerevision and postrevision shunt volume flow. Volume flow was computed offline based on the principle of surface integration of Doppler‐measured velocity vectors in a lateral‐elevational c‐surface positioned at the color flow focal depth (range, 8.0–11.5 cm). Volume flow was compared to routine measurements of the prerevision and postrevision portosystemic pressure gradient. Prerevision volume flow was compared with the outcome to determine whether a flow threshold for revision could be defined. Results: Linear regression of data from revised transjugular intrahepatic portosystemic shunt cases showed an inverse correlation between the mean‐normalized change in prerevision and postrevision shunt volume flow and the mean‐normalized change in the prerevision and postrevision portosystemic pressure gradient ( r 2 = 0.51; P = .020). Increased shunt blood flow corresponded to a decreased pressure gradient. Comparison of prerevision flows showed preliminary threshold development at 1534 mL/min, below which a shunt revision may be recommended ( P = .21; area under the receiver operating characteristic curve = 0.78). Conclusions: Shunt volume flow measurement with 3D/4D Doppler sonography provides a potential alternative to standard pulsed wave Doppler metrics as an indicator of shunt function and predictor of revision.